EKSISTENSI KEWENANGAN BALAI HARTA PENINGGALAN ATAS ORANG YANG DINYATAKAN TIDAK HADIR (AFWEZIGHEID) - Bidasari, Anindya (Jurnal Panorama Hukum, 2016)
Inherited Property Board in Indonesia until now the existence of authority if not viewed by the public. As the government agency within the Ministry of Justice and Human Rights of the Republic of Indonesia, the Civil Directorate, one of the tasks BHP is to represent the interests of those who are not present and difficult to find or in legal terms is called afwezigheid was instrumental in carrying out the maintenance and management of the property that the owner is declared absent or difficult to find. In determining the absence that can be simultaneously appointed BHP locals who will be in charge of and which represent and defend all the interests of the absentee that during his absence, but without prejudice to the authority of a judge to appoint one or more of the family by blood or marriage of the absentee or to the wife or husband for that purpose (Article 463 paragraph (3) of the Civil Code). This research is legal (normative). The approach will be used in this legal research involved the Statute Approach (approach legislation) and Conceptual Approach (Approach Concept). The results of this study indicate that during this Hall Heritage memili existence of duties and authority as pengampu on people who were not present, the process of absence, there are three stages: (a) The decision of provisional measures, (b) The allegation of law may have died, (c) future Inheritance derivatives, and supported by the District Court case that there is Decision No. 15 / Pdt.P / 2014 / PN.Kdi's absence in inheritance. In line with this Court decision the judge should also assign tasks to BHP as pengampu on people who otherwise may not be present. Because BHP like lawyers resolve the legal issues in the field of assets and management of property from a person who declared no existence hadir.Namun operation of BHP still needed a strong mastery of the Civil Code as well as the community's understanding of BHP.